Building high performance in state-owned enterprises: A structural model of organizational climate, learning, and knowledge sharing - Cipta, Hendra; Brahmasari, Ida Aju; Ratih, Ida Aju Brahma (Edelweiss Applied Science and Technology, 2026)
This study examines the structural relationships among Organizational Climate, Organizational Learning, Knowledge Sharing, and High Performance in State-Owned Enterprises (SOEs). Using a quantitative explanatory design, data were collected through structured questionnaires from 350 employees of Indonesian SOEs and analyzed using Partial Least Squares Structural Equation Modeling (PLS-SEM) with SmartPLS 4.0. The results show that Organizational Climate has a significant positive effect on Organizational Learning, Knowledge Sharing, and High Performance. Knowledge Sharing also significantly influences performance, whereas Organizational Learning does not have a direct effect. Mediation analysis indicates that Knowledge Sharing partially mediates the relationship between Organizational Climate and High Performance. These findings highlight the importance of a supportive organizational climate in fostering knowledge-sharing behaviors to enhance performance. This study contributes to organizational behavior literature in the public sector and provides practical insights for leaders and policymakers to strengthen climate-building strategies for sustainable performance in SOEs.